Models for dark matter and neutrino masses (2017)
ABSTRACT: "This thesis includes the study of novel models that account for neutrino masses and mixing and provide a viable candidate for the DM in the Universe. For the electroweak extension of the SM based on the SU(3)C (producto tensor) SU(4)L (producto tensor) U(1)X gauge group, several mechanisms for the neutrino mass generation through the tree-level realization of a dimension five Weinberg-like operator are proposed. For the so called model F, a three-family model, is found that the mixing matrix and mass hierarchy for the lightest neutrinos (the SM ones) and the exotic neutrinos (the heavy ones) turns out to be the same. For the radiative type III seesaw model - a kind of scotogenic model - a collider study carried out in a simplify scenario, with scalar dark matter. Limits on the fermion triplet masses are set as a function of the flavor."